Photonic orbital angular momentum transfer and magnetic skyrmion rotation - Yang, Wenrui; Yang, Huanhuan; Cao, Yunshan; Yan, Peng (Optics express, 2018)
Magnetic skyrmions are chiral quasiparticles that show promise for future spintronic applications such as skyrmion racetrack memories and logic devices because of their topological stability, small size (typically ∼ 3 - 500 nm), and ultralow threshold force to drive their motion. On the other hand, the ability of light to carry and deliver orbital angular momentum (OAM) in the form of optical vortices has attracted a lot of interest. In this work, we predict a photonic OAM transfer effect, by studying the dynamics of magnetic skyrmions subject to Laguerre-Gaussian optical vortices, which manifests a rotational motion of the skyrmionic quasiparticle around the beam axis. The topological charge of the optical vortex determines both the magnitude and the handedness of the rotation velocity of skyrmions. In our proposal, the twisted light beam acts as an optical tweezer to enable us displacing skyrmions over large-scale defects in magnetic films to avoid being captured.